Die limitierte Auflage: Rechtsfragen zeitgenössischer Fotokunst - M Michl, Felix (Heidelberg University Publishing (heiUP), 2016)
Over the course of the past decades, photography has become one of the most popular fields of art. This development is also reflected in recent prices for some works of contemporary photography, which fetch up to several million dollars. Such price levels would be unheard of if artists were to take advantage of the opportunity to produce as many prints from the same negative as possible. On the contrary, the prevailing practice in contemporary photography is that of printing photographs in "limited editions", with some of the most expensive photographs only existing in the low single digits. This study researches the legal implications of artists communicating limited editions to the purchasers of their art with the main question being whether such "promises of exclusivity" are legally binding and thus could be enforced by collectors e. g. in court proceedings.